Prevalence of failure of passive transfer of immunoglobulins in Holstein calves in Northern Greece and association with management practices - PANOUSIS (Ν. ΠΑΝΟΥΣΗΣ), N.; KRITSEPI- KONSTANTINOU (Μ. ΚΡΙΤΣΕΠΗ-ΚΩΝΣΤΑΝΤΙΝΟΥ), M.; KALAITZAKIS (Ε. ΚΑΛΑΪΤΖΑΚΗΣ), E.; GIADINIS (Ν. ΓΙΑΔΙΝΗΣ), N.; VALERGAKIS (Γ.Ε. ΒΑΛΕΡΓΑΚΗΣ), G. E. (Journal of the Hellenic Veterinary Medical Society, 2017)
Objectives of the present study were to estimate prevalence of failure of passive transfer of immunoglobulins in dairy calves in Northern Greece and to investigate factors potentially associated with it. Four hundred and thirty seven clinically healthy calves in 30 farms were included in the study. Age of calves was 18 h to 7 d. Animals were blood sampled and serum total protein concentrations were measured by a refractometer. Two thresholds of total protein concentration were used: 5.2 or 5.5 g dL 1. At calf level, an animal was considered to have failure of passive transfer of immunoblobulins when total protein concentrations were lower than the above thresholds. At herd level, a herd was considered to have failure of passive transfer of immunoglobulins when >20% of sampled calves had total protein concentration was <5.2 or <5.5 g dL-1. Moreover, data on health management on the farm were collected in a purpose-built questionnaire. At 5.2 g dL-1, 20% of the calves and 40% of the herds were considered to have failure of passive transfer of immunoglobulins; when the 5.5 g dL-1 threshold was used, respective prevalences were 26% and 53%. At herd level, mean blood serum total protein concentration tended to be positively affected by a short interval between birth and first colostrum meal, by maintenance of a stock of frozen colostrum and by establishment of a close-up group of dry cows. At calf level, the same factors had a statistically significant positive effect on blood serum total protein concentration. Moreover, quantity of colostrum received by calves and colostrum condition were also positively related with blood serum total protein concentration. In conclusion, failure of passive transfer of immunoglobulins is a common problem in Holstein calves in Northern Greece. Increased prevalence of the problem implies that increased efforts and management practices need to be applied to ensure the adequate transfer of maternal immunoglobulins to newborn calves. Also, it becomes obvious from all the above findings that many farmers are not well informed for management practices that have to implement to ensure adequate amounts of immunoglobulins to newborn calves. Hence, dissemination of knowledge concerning best management practices for achieving adequate passive immunity is considered to be of significant importance.